China’s Assertive Foreign Policy in South China Sea Under Xi Jinping: Its Impact on United States and Australian Foreign Policy - Sinaga, Lidya Christin (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2015)
This essay examines the impact of the assertiveness of China’s Foreign Policy in the South China Sea under Xi Jinping on United States and Australian foreign policy. The essay focuses on the Xi Jinping period from 2013 because Xi has a different approach in foreign policy making from that of his predecessors. His determination to defend and advance maritime claims and interests as well as the external developments, have made his foreign policy more assertive. This essay will argue that China’s assertive foreign policy in South China Sea under Xi Jinping has paved the way for a greater role for the US in Southeast Asia, and deepened the rivalry between China and the US. This rising tension in turn has put Australia in a challenging situation, torn between its security alliance with the United States, and its economic interests in China. However, Australia does not have to choose one, but Australia can play a constructive role in the development of some compromise between the two.